Comparative Evaluation of the Tensile Bond Strength of Custom and Pre-Fabricated Posts - An in Vitro Study - Heena Fuletra; Kamal Bagda; Suman Makam; Kruti Patel; Niket Kachhi (Advances in Human Biology, 2014)
Aim: To evaluate the effect of cyclic loading on the tensile bond strength and retention of custom ‑fabricated cast posts, prefabricated metal posts and glass fiber posts. Materials and Method: Thirty extracted human maxillary central incisors were decoronated at the cementoenamel junction (CEJ) and randomly divided into three groups (n=10). Specimens were instrumented and obturated. Twenty four hours after obturation, post space was prepared upto no. 5 Peeso Reamer. Groups A, B and C were restored using custom cast post and core, Para Post (Whale dent) and Reforpost (Angelus) respectively thereafter. Five specimens from each group were subjected to cyclic loading. Tensile bond strength (TBS) of teeth before and after cyclic loading was evaluated. Results: For both, with and without loading, Groups A and B were not significantly different from each other but Group C was significantly different from Groups A and B. The results indicated that cyclic loading reduces retention potential of all three types of post, but it was minimum in group C. Conclusions: Cyclic loading reduced the retention of all posts but was comparatively lesser for the glass fiber post. This system provides sufficient retention required for clinical success.